Aplication of Sweet Maize Whole Plant Silage (Zea mays saccharata Sturt) and Gliricia sepium for Feed of Dairy Cattle - Riesi Sriagtula; Qurrata Aini; Hilda Susanty; Yetmaneli Yetmaneli (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The low productivity of smallholder dairy cattle in Indonesia is due to limited capital and feed management. Limited land ownership, resulting in feeding from low-quality natural grasses and agricultural waste, limits milk production. Farmers rely on expensive commercial concentrate feed to improve feed quality. Efforts to improve productivity and milk quality on smallholder farms include utilizing low-cost, high-nutrient forages. Legume forages have the potential to replace commercial concentrates in dairy cow rations because they contain high crude protein (CP) and can increase livestock productivity. Using legumes as a substitute for commercial concentrates can reduce milk production costs by up to 20%. In Indonesia, the most widely cultivated legume crop is Gliricidia. Harapan Makmur Farmer Group is one of the few dairy cattle groups established in Padang City in 2011. The problem of the dairy cattle business is the high feed price, some of which comes from commercial feed. The activity method uses counseling, discussion, and the practice of making sweet corn silage mixed with Gliricidia. These activities concluded that farmers were utilizing forage from legumes to substitute commercial concentrates, and they were skilled in processing corn straw waste from sweet corn cultivation and Gliricidia into silage.